Deepening Health Reform in China : Building High-Quality and Value-Based Service Delivery - World Bank Group (Washington, DC: World Bank, 2016)
At a meeting in July 2014 in Beijing, we committed to working together on a flagship report that would help set the direction for health sector reform in China. This report, Deepening Health Reform in China, is the result. Using the successful model offered by previous flagship reports like China 2030 and Urban China, this report primarily offers a blueprint for a new direction for China’s health sector. The report’s main theme is the need for China to transition its healthcare delivery system toward people-centered, quality, integrated care built on the foundation of a strong primary healthcare system.